A battery cell, a method of manufacturing the same, a secondary battery, and an electric device
Patent Information
- Application Number
- CN202510428251.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2026-10-16
Smart Images

Figure CN122931055A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of secondary battery technology, specifically to a battery cell and its preparation method, a secondary battery, and an electrical device. Background Technology
[0002] As the requirements for secondary battery capacity continue to increase, the height of the electrode components in secondary batteries is constantly increasing, while the amount of electrolyte injected is decreasing, leading to an increasingly prominent problem of secondary batteries experiencing rapid degradation during cycling. Summary of the Invention
[0003] In view of the above problems, this application provides a battery cell and its preparation method, as well as a secondary battery electrical device, which can improve the problem of low cycling performance in secondary batteries.
[0004] In a first aspect, this application provides a battery cell, which includes a positive electrode, a separator, a negative electrode, and an electrolyte. The separator includes a base film and a first coating and a second coating respectively located on the surface of the base film; the first coating is disposed between the positive electrode and the base film, and the second coating is disposed between the negative electrode and the base film; the electrolyte is in contact with at least a portion of the positive electrode, the separator, and the negative electrode. The roughness Ra of the second coating is greater than the roughness Ra of the first coating.
[0005] In the technical solution of this application embodiment, by controlling the roughness of the second coating to be greater than that of the first coating, the capillary effect formed between the second coating and the negative electrode is stronger than that formed between the first coating and the positive electrode. The liquid creeping channel formed between the second coating and the negative electrode is better than that formed between the first coating and the positive electrode. As a result, the liquid absorption rate on the negative electrode side is greater than that on the positive electrode side, which can match the electrolyte requirements of the negative and positive electrodes, quickly replenish the electrolyte on the negative electrode side, make full use of the electrolyte, and improve the cycle performance of the secondary battery.
[0006] In some embodiments, the difference between the roughness Ra of the second coating and the roughness Ra of the first coating ranges from 0.25 μm to 1.85 μm.
[0007] In the above implementation process, by controlling the difference between the roughness Ra of the second coating and the roughness Ra of the first coating to be within the range of 0.25μm to 1.85μm, it is possible to better match the different requirements of the negative electrode and the positive electrode for electrolyte, so that the electrolyte can be utilized more fully, thereby further reducing the use of electrolyte and improving the cycle performance of the secondary battery.
[0008] In some embodiments, the roughness Ra of the second coating is 0.4 μm to 2.0 μm; and / or
[0009] The roughness Ra of the first coating is 0.15 μm to 0.5 μm.
[0010] In the above implementation process, by controlling the roughness Ra of the second coating to be 0.4 μm to 2.0 μm and the roughness Ra of the first coating to be 0.15 μm to 0.5 μm, both the negative and positive electrode sheets can be well wetted, reducing the probability of active metal deposition and thus improving the cycle performance of the secondary battery. Furthermore, it can match the electrolyte requirements of the negative and positive electrode sheets, ensuring full utilization of the electrolyte and reducing electrolyte usage.
[0011] In some embodiments, the first coating comprises a first polymeric material, and the second coating comprises a second polymeric material and inorganic particles.
[0012] In the above implementation process, inorganic particles can give the second coating a better roughness, and a capillary effect is formed between the second coating and the negative electrode, creating a liquid creep channel. This allows the electrolyte to be quickly replenished through the gap between the second coating and the negative electrode, thereby enhancing the liquid absorption rate of the second coating.
[0013] In some embodiments, the first coating includes a first polymeric adhesive layer, the first polymeric adhesive layer includes a first polymeric material, and the first polymeric material accounts for more than 90% of the mass of the first polymeric adhesive layer.
[0014] The second coating comprises an inorganic particle coating and a second polymer adhesive layer. The inorganic particle coating comprises inorganic particles, and the inorganic particles account for more than 90% of the mass of the inorganic particle coating. The second polymer adhesive layer comprises a second polymer material, and the second polymer material accounts for more than 90% of the mass of the second polymer adhesive layer.
[0015] In the above implementation process, by layering polymer materials and inorganic particles, it is more conducive to the preparation of the diaphragm, thereby enabling the industrial production of the diaphragm.
[0016] In some embodiments, the coating amount of the inorganic particles is 0.01 mg / 1540.25 mm. 2 ~1.25mg / 1540.25mm 2 ; and / or
[0017] The coating amount of the second polymer adhesive layer is 0.25 mg / 1540.25 mm. 2 ~0.5mg / 1540.25mm 2 .
[0018] In some embodiments, the inorganic particle coating is disposed between the second polymer adhesive layer and the separator base film.
[0019] In the above implementation process, by placing the second polymer adhesive layer on the outer side, it can cooperate with the negative electrode sheet, which is beneficial to the assembly of the negative electrode sheet and the separator.
[0020] In some embodiments, the coating amount of the first coating is 0.25 mg / 1540.25 mm. 2 ~0.5mg / 1540.25mm 2 ; and / or
[0021] The second coating was applied at a rate of 0.5 mg / 1540.25 mm. 2 ~1.5mg / 1540.25mm 2 ; and / or
[0022] The median particle size Dv50 of the inorganic particles is 0.5 μm to 5 μm.
[0023] In the above implementation process, the coating amount of the first coating is controlled to be 0.25 mg / 1540.25 mm. 2 ~0.5mg / 1540.25mm 2 The second coating has a coating weight of 0.5 mg / 1540.25 mm. 2 ~1.5mg / 1540.25mm 2 The median particle size Dv50 of the inorganic particles is 0.5μm to 5μm, which allows the liquid absorption rate of the first coating and the liquid absorption rate of the second coating to be well matched with the electrolyte requirements of the negative electrode and the positive electrode, so that the electrolyte can be fully utilized, thereby reducing the use of electrolyte and improving the cycle performance of the secondary battery.
[0024] In some embodiments, the first polymeric material includes at least one selected from nitrile rubber, polyvinyl chloride, polypropylene, polyvinyl alcohol, polyethylene, or polyvinylidene fluoride polymer; and / or
[0025] Inorganic particles include at least one of boehmite, silica, magnesium hydroxide, alumina, zirconium oxide, magnesium oxide, mullite, or cordierite; and / or
[0026] The second polymeric material includes at least one of nitrile rubber, polyvinyl chloride, polypropylene, polyvinyl alcohol, polyethylene, or polyvinylidene fluoride polymer.
[0027] In some embodiments, the relationship between the electrolyte absorption rate *a* of the first coating and the electrolyte absorption rate *b* of the second coating satisfies: 0 mm / s 0.5 <ba≤5mm / s 0.5 .
[0028] In the above implementation process, the difference in electrolyte absorption rate between the second coating and the first coating is controlled to be between 0 and 5 mm / s.0.5 This allows for better matching of the electrolyte requirements of the negative and positive electrode plates, enabling more efficient use of the electrolyte and further reducing electrolyte consumption.
[0029] In some embodiments, the electrolyte absorption rate α of the first coating is 0.1 mm / s. 0.5 ~2mm / s 0.5 ; and / or
[0030] The second coating has an electrolyte absorption rate b of 2 mm / s. 0.5 ~5mm / s 0.5 .
[0031] In the above implementation process, the absorption rate 'a' of the first coating on the electrolyte is controlled to be 0.1 mm / s. 0.5 ~2mm / s 0.5 The second coating has an electrolyte absorption rate b of 2 mm / s. 0.5 ~5mm / s 0.5 It can better match the electrolyte requirements of the negative and positive electrode plates, making full use of the electrolyte, thereby reducing the use of electrolyte and improving the cycle performance of the secondary battery.
[0032] In some embodiments, the height of the positive electrode sheet along the first direction X is not less than 100 mm; and / or
[0033] Along the first direction X, the height of the negative electrode sheet is not less than 100mm.
[0034] In the above implementation process, the higher the height of the electrode sheet, the greater the probability of active metal precipitation at its top, and the more likely the phenomenon of cyclic water drop will occur. However, by setting a first coating and a second coating on both surfaces of the base film, both the positive and negative electrode sheets are properly wetted, which can effectively improve the problem of active metal precipitation in taller electrode sheets, thereby improving the problem of cyclic water drop.
[0035] In some embodiments, the height of the positive electrode sheet along the first direction X is 100mm to 600mm; and / or
[0036] Along the first direction X, the height of the negative electrode plate is 100mm to 600mm.
[0037] In some embodiments, the amount of electrolyte used is 2.0 g / Ah to 6.0 g / Ah.
[0038] In the above implementation process, by differentiating the first coating and the second coating, the electrolyte requirements of the high-strength negative electrode and positive electrode can be matched, so that the electrolyte can be fully utilized and the use of electrolyte can be reduced.
[0039] Secondly, this application provides a method for preparing a battery cell, the method comprising:
[0040] The first polymer material is formulated into a first slurry;
[0041] The second polymer material and inorganic particles are formulated into a second slurry;
[0042] The first slurry and the second slurry are respectively coated on both sides of the base film to form the first coating and the second coating, respectively, to obtain a separation film, wherein the roughness of the second coating is greater than that of the first coating.
[0043] A separator, a positive electrode, and a negative electrode are assembled, and an electrolyte is brought into contact with at least a portion of the positive electrode, the separator, and the negative electrode to obtain a battery cell. A first coating is disposed between the positive electrode and the base film, and a second coating is disposed between the negative electrode and the base film.
[0044] Thirdly, this application provides a secondary battery, which includes the battery cell provided in the first aspect or the battery cell obtained by the method provided in the second aspect.
[0045] Fourthly, this application provides an electrical device, which includes a battery cell provided in the first aspect, a battery cell obtained by the method provided in the second aspect, or a secondary battery provided in the third aspect. Attached Figure Description
[0046] Various other advantages and benefits will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiments below. The accompanying drawings are for illustrative purposes only and are not intended to limit the scope of this application. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings:
[0047] Figure 1 This is a schematic diagram of the structure of an electrode assembly provided in some embodiments of this application;
[0048] Figure 2 Flowcharts of methods provided in some embodiments of this application;
[0049] Figure 3 This is a schematic diagram of the structure of a battery cell provided in some embodiments of this application;
[0050] Figure 4 Exploded views of a single battery cell provided in some embodiments of this application;
[0051] Figure 5 This is an exploded structural diagram of a secondary battery provided in some embodiments of this application;
[0052] Figure 6The diagram shows the structure of a vehicle provided in some embodiments of this application.
[0053] The reference numerals in the detailed embodiments are as follows:
[0054] 1000 - Vehicle; 100 - Secondary battery; 200 - Motor; 300 - Controller; 10 - Housing; 11 - Accommodation space; 12 - First part; 13 - Second part; 20 - Battery cell; 21 - Shell; 211 - Opening; 22 - End cap assembly; 221 - End cap; 222 - Electrode terminal; 23 - Electrode assembly; 231 - Separator; 2311 - Base film; 2312 - First coating / first polymer adhesive layer; 2313 - Second coating; 2313a - Inorganic particle coating; 2313b - Second polymer adhesive layer; 232 - Positive electrode; 233 - Negative electrode; 24 - Current collector; 25 - Insulation protection component. Detailed Implementation
[0055] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0056] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0057] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.
[0058] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0059] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0060] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces).
[0061] In the description of the embodiments of this application, the technical terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing the embodiments of this application and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of this application.
[0062] In the description of the embodiments of this application, unless otherwise expressly specified and limited, technical terms such as "installation," "connection," "joining," and "fixing" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. For those skilled in the art, the specific meaning of the above terms in the embodiments of this application can be understood according to the specific circumstances.
[0063] Currently, judging from market trends, the application of power batteries is becoming increasingly widespread. Power batteries are not only used in energy storage systems such as hydropower, thermal power, wind power, and solar power plants, but also extensively used in electric vehicles such as electric bicycles, electric motorcycles, and electric cars, as well as in military equipment and aerospace. With the continuous expansion of power battery applications, market demand is also constantly increasing.
[0064] As the requirements for secondary battery capacity continue to increase, the height of the electrode components of secondary batteries is constantly increasing (e.g., high-capacity cells, with a height of >150mm in the first direction X), while the amount of electrolyte injected is decreasing, leading to an increasingly prominent problem of secondary batteries experiencing rapid degradation during cycling.
[0065] Without any theoretical constraints, it was found that the cycle failure is related to insufficient electrolyte wetting at the electrode assembly head. As cycling progresses, the large height of the electrode assembly head prevents the electrolyte from reaching the head in time, hindering the migration of active metal ions and causing active metal deposition on the electrode surface, resulting in active metal loss and thus causing the secondary battery to fail during cycling. Furthermore, considering that the active material of the negative electrode inevitably expands during secondary battery cycling, leading to SEI film rupture and the formation of a fresh negative electrode active material interface, a new SEI film needs to be formed. The electrolyte on the negative electrode is continuously consumed, requiring continuous replenishment to ensure adequate wetting of the negative electrode during cycling.
[0066] Among them, active metal refers to the metal material that can be inserted and extracted from the positive electrode active material during the charging and discharging process of secondary battery. For example, the active metal of lithium-containing positive electrode active material is lithium, and the active metal of sodium-containing positive electrode active material is sodium.
[0067] Based on the above considerations, to improve the problem of low cycle life in secondary batteries, this application proposes a battery cell, which includes a positive electrode, a separator, a negative electrode, and an electrolyte. The separator includes a base film and a first coating and a second coating respectively located on both surfaces of the base film; the positive electrode is disposed on the separator near the first coating; the negative electrode is disposed on the separator near the second coating; the electrolyte is in contact with at least a portion of the positive electrode, the separator, and the negative electrode. The roughness Ra of the second coating is greater than the roughness Ra of the first coating.
[0068] This battery cell controls the roughness of the second coating to be greater than that of the first coating, resulting in a stronger capillary effect between the second coating and the negative electrode than between the first coating and the positive electrode. The liquid creeping channel between the second coating and the negative electrode is superior to that between the first coating and the positive electrode, thus enabling a higher liquid absorption rate on the negative electrode side than on the positive electrode side. This matches the electrolyte requirements of both the negative and positive electrodes, allowing for rapid replenishment of electrolyte on the negative electrode side and ensuring full utilization of the electrolyte, thereby improving the cycle performance of the secondary battery.
[0069] This application provides a battery cell 20, which includes a positive electrode 232, a separator 231, a negative electrode 233, and an electrolyte. The separator 231 includes a base film 2311 and a first coating 2312 and a second coating 2313 respectively located on the surface of the base film 2311. Figure 1 For schematic diagrams illustrating the assembly of the separator 231 and electrode sheets into the electrode assembly 23 according to some embodiments of this application, please refer to [link / reference]. Figure 1The first coating 2312 is disposed between the positive electrode 232 and the base film 2311, and the second coating 2313 is disposed between the negative electrode 233 and the base film 2311; the electrolyte is in contact with at least a portion of the positive electrode 232, the separator 231, and the negative electrode 233, respectively. The roughness Ra of the second coating 2313 is greater than the roughness Ra of the first coating 2312.
[0070] Surface roughness refers to the unevenness of a surface, characterized by small gaps and minute peaks and valleys. The distance between two peaks or valleys (wavelength) is very small (less than 1 mm), belonging to microscopic geometric shape errors. Surface roughness is measured using a laser online thickness gauge according to the following standard: GB / T 1031-2009 Surface Structure Profiling Method: Surface Roughness Parameters and Their Values.
[0071] The battery cell 20 controls the roughness of the second coating 2313 to be greater than that of the first coating 2312, so that the capillary effect formed between the second coating 2313 and the negative electrode 233 is stronger than that formed between the first coating 2312 and the positive electrode 232. The liquid creeping channel formed between the second coating 2313 and the negative electrode 233 is better than that formed between the first coating 2312 and the positive electrode 232. As a result, the liquid absorption rate on the negative electrode side is greater than that on the positive electrode side, which can match the electrolyte requirements of the negative electrode 233 and the positive electrode 232, and quickly replenish the electrolyte on the negative electrode side, so that the electrolyte is fully utilized and the cycle performance of the secondary battery 100 can be improved.
[0072] The liquid absorption rate of the positive electrode side (the positive electrode side is formed by the combination of the separator 231 and the positive electrode plate 232) or the negative electrode side (the positive electrode side is formed by the combination of the separator 231 and the negative electrode plate 233) can be expressed by its liquid absorption rate of the electrolyte. The liquid absorption rate refers to the height that the electrolyte can climb in the positive or negative electrode side per unit time. The test process can be as follows: after the separator 231 and the electrode plate are combined, they are placed in an acrylic mold and pressurized to 0.2MPa. Then, the acrylic mold is immersed in 1mm to 2mm of electrolyte to test the liquid absorption rate. The climbing height is recorded at regular intervals. Then, the square root of time is plotted to obtain the liquid absorption rate graph with the height as the vertical axis and the square root of seconds as the horizontal axis. The liquid absorption rate of the coating to the electrolyte can be obtained. It should be noted that during the test, the liquid absorption rate of the positive electrode side and the negative electrode side are tested separately. For example, when testing the liquid absorption rate of the positive electrode side, the positive electrode 232 is bonded to the side of the separator 231 where the first coating 2312 is provided for testing; when testing the liquid absorption rate of the negative electrode side, the negative electrode 233 is bonded to the side of the separator 231 where the second coating 2313 is provided for testing.
[0073] In the technical solution of this application embodiment, the difference between the roughness Ra of the second coating and the roughness Ra of the first coating ranges from 0.25 μm to 1.85 μm. By controlling the difference between the roughness Ra of the second coating and the roughness Ra of the first coating to be within the range of 0.25 μm to 1.85 μm, the difference in electrolyte requirements between the negative electrode and the positive electrode can be better matched, allowing for more efficient utilization of the electrolyte. This further reduces the use of electrolyte and improves the cycle performance of the secondary battery.
[0074] For example, the difference between the roughness Ra of the second coating and the roughness Ra of the first coating can be 0.25μm, 0.35μm, 0.45μm, 0.55μm, 0.65μm, 0.75μm, 0.85μm, 0.95μm, 1.05μm, 1.15μm, 1.25μm, 1.35μm, 1.45μm, 1.55μm, 1.65μm, 1.75μm, or 1.85μm, etc., or it can be any value in the range of 0.25μm to 1.85μm.
[0075] In the technical solution of this application embodiment, the roughness Ra of the second coating is 0.4 μm to 2.0 μm; the roughness Ra of the first coating is 0.15 μm to 0.5 μm. By controlling the roughness Ra of the second coating to be 0.4 μm to 2.0 μm and the roughness Ra of the first coating to be 0.15 μm to 0.5 μm, both the negative and positive electrode sheets can be well wetted, reducing the probability of active metal deposition and thus improving the cycle performance of the secondary battery. Furthermore, it can match the electrolyte requirements of the negative and positive electrode sheets, allowing for full utilization of the electrolyte and reducing electrolyte usage.
[0076] For example, the roughness Ra of the second coating can be 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, etc., or any value within the range of 0.4 μm to 2.0 μm. The roughness Ra of the first coating can be 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, etc., or any value within the range of 0.15 μm to 0.5 μm.
[0077] In the technical solution of this application embodiment, the first coating includes a first polymer material, and the second coating includes a second polymer material and inorganic particles.
[0078] Inorganic particles refer to particles composed of inorganic materials, which can increase surface roughness, thereby enabling the separator and electrode plates to form better liquid absorption channels and improve the liquid absorption rate.
[0079] In the technical solution of this application embodiment, the first coating includes a first polymer adhesive layer 2312, the first polymer adhesive layer 2312 includes a first polymer material, and the mass proportion of the first polymer material in the first polymer adhesive layer 2312 is more than 90%.
[0080] The second coating includes an inorganic particle coating 2313a and a second polymer adhesive layer 2313b. The inorganic particle coating 2313a includes inorganic particles, and the inorganic particles account for more than 90% of the mass of the inorganic particle coating 2313a. The second polymer adhesive layer 2313b includes a second polymer material, and the second polymer material accounts for more than 90% of the mass of the second polymer adhesive layer 2313b.
[0081] In the above text, "the first polymeric material accounts for more than 90% of the mass of the first polymeric adhesive layer 2312" means that the majority of the material in the first polymeric adhesive layer 2312 is the first polymeric material, and other similar descriptions have the same meaning. Furthermore, the first polymeric adhesive layer 2312 and the second polymeric adhesive layer 2313b can be composed of pure polymeric materials, and their thicknesses can be the same or different. Usually, for ease of preparation, the thicknesses of the first polymeric adhesive layer 2312 and the second polymeric adhesive layer 2313b can be the same. It is understood that when the first coating 2312 contains both polymeric particles and porous inorganic particles, the polymeric material and inorganic particles can also be arranged in layers, as described in the above description of the second coating 2313. Of course, the first polymeric adhesive layer 2312 and the second polymeric adhesive layer 2313b can also contain a small amount of inorganic particles, and the inorganic particle coating 2313a can also contain a small amount of polymeric material.
[0082] The mass ratio of polymeric materials and inorganic particles in the first coating 2312 and the second coating 2313 can be tested by thermogravimetric analysis. Specifically, the first coating 2312 or the second coating 2313 is placed in the sample chamber of the thermogravimetric analyzer, the instrument is started, and the temperature is increased to 1000℃ at a rate of 1℃ / min. The weight loss after the polymer decomposes due to heat is the mass ratio of polymeric materials. The rest of the polymeric materials are inorganic particles, and the corresponding mass ratio of inorganic particles is obtained.
[0083] By layering polymer materials and inorganic particles, it is more conducive to the preparation of the membrane, thereby enabling the industrial production of the membrane.
[0084] In other embodiments, the second coating 2313 may not be layered, but rather a single layer is prepared by mixing polymeric materials and inorganic particles.
[0085] In the technical solution of this application embodiment, the coating amount of the inorganic particle coating is 0.01mg / 1540.25mm. 2 ~1.25mg / 1540.25mm 2 The coating amount of the second polymer adhesive layer is 0.25 mg / 1540.25 mm. 2 ~0.5mg / 1540.25mm 2 .
[0086] For example, the coating amount of the inorganic particles can be 0.01 mg / 1540.25 mm. 2 0.1mg / 1540.25mm 2 0.2mg / 1540.25mm 2 0.3mg / 1540.25mm 2 0.4mg / 1540.25mm 2 0.5mg / 1540.25mm 2 0.6mg / 1540.25mm 2 0.7mg / 1540.25mm 2 0.8mg / 1540.25mm 2 0.9mg / 1540.25mm 2 1mg / 1540.25mm 2 1.1mg / 1540.25mm 2 1.2mg / 1540.25mm 2 Or 1.25mg / 1540.25mm 2 It can also be 0.01 mg / 1540.25 mm. 2 ~1.25mg / 1540.25mm 2 Any value within the range. The coating amount of the second polymer adhesive layer can be 0.25 mg / 1540.25 mm. 2 0.3mg / 1540.25mm 2 0.35mg / 1540.25mm 2 0.4mg / 1540.25mm 2 0.45mg / 1540.25mm 2 0.5mg / 1540.25mm 2 It can also be 0.25mg / 1540.25mm. 2 ~0.5mg / 1540.25mm2 Any value within the range.
[0087] In the technical solution of this application embodiment, the inorganic particle coating 2313a is disposed between the second polymer adhesive layer 2313b and the separator base film. By disposing the second polymer adhesive layer 2313b on the outer side, it can cooperate with the negative electrode 233, which is beneficial to the assembly of the negative electrode and the separator.
[0088] In the technical solution of this application embodiment, the coating amount of the first coating is 0.25mg / 1540.25mm. 2 ~0.5mg / 1540.25mm 2 The second coating was applied at a rate of 0.5 mg / 1540.25 mm. 2 ~1.5mg / 1540.25mm 2 The median particle size Dv50 of the inorganic particles is 0.5 μm to 5 μm.
[0089] The median particle size Dv50 is the particle size corresponding to 50% of the cumulative amount in the volumetric particle size distribution map. The volumetric particle size distribution map, also known as the differential particle size distribution map, is a curve plotted with particle size on the x-axis and the differential distribution of particle size at different dimensions on the y-axis. It can accurately reflect the particle size distribution characteristics of a material. A laser particle size analyzer can be used to determine the volumetric particle size distribution of the material and plot the interval particle size distribution curve. When measuring the median particle size of inorganic particles in the coating of a release liner, the coating can be removed, immersed in the solvent NMP, and the binder in the coating can be washed out to obtain the coating powder material. After drying the powder material, a Mastersizer 3000 laser particle size analyzer is used to detect the volumetric particle size distribution map. The median particle size of the inorganic particles can be obtained from the peaks in the volumetric particle size distribution map.
[0090] By controlling the coating amount of the first coating 2312 to 0.25 mg / 1540.25 mm 2 ~0.5mg / 1540.25mm 2 The coating amount of the second coating 2313 is 0.5 mg / 1540.25 mm. 2 ~1.5mg / 1540.25mm 2 The Dv50 of the inorganic particles is 0.5μm to 5μm, which allows the liquid absorption rate on the positive electrode side and the liquid absorption rate on the negative electrode side to be better matched with the electrolyte requirements of the negative electrode 233 and the positive electrode 232, so that the electrolyte can be fully utilized, thereby reducing the use of electrolyte and improving the cycle performance of the secondary battery 100.
[0091] For example, the coating amount of the first coating 2312 can be 0.25 mg / 1540.25 mm. 2 0.3mg / 1540.25mm 2 0.35mg / 1540.25mm 2 0.4mg / 1540.25mm 2 0.45mg / 1540.25mm 2 0.5mg / 1540.25mm 2 It can also be 0.25mg / 1540.25mm. 2 ~0.5mg / 1540.25mm 2 Any value within the range. The coating amount of the second coating 2313 can be 0.5 mg / 1540.25 mm. 2 0.55mg / 1540.25mm 2 0.6mg / 1540.25mm 2 0.65mg / 1540.25mm 2 0.7mg / 1540.25mm 2 0.75mg / 1540.25mm 2 0.8mg / 1540.25mm 2 0.85mg / 1540.25mm 2 0.9mg / 1540.25mm 2 0.95mg / 1540.25mm 2 1mg / 1540.25mm 2 1.05mg / 1540.25mm 2 1.1mg / 1540.25mm 2 1.15mg / 1540.25mm 2 1.2mg / 1540.25mm 2 1.25mg / 1540.25mm 2 1.3mg / 1540.25mm 2 1.35mg / 1540.25mm 2 1.4mg / 1540.25mm 2 1.45mg / 1540.25mm 2 1.5mg / 1540.25mm 2 It can also be 0.5mg / 1540.25mm. 2 ~1.5mg / 1540.25mm 2The Dv50 of inorganic particles can be any value within the range of 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, etc., or any value within the range of 0.5μm to 5μm.
[0092] In the technical solution of this application embodiment, the first polymeric material includes at least one selected from nitrile rubber, polyvinyl chloride, polypropylene, polyvinyl alcohol, polyethylene, or polyvinylidene fluoride polymer. The inorganic particles include at least one selected from boehmite, silica, magnesium hydroxide, alumina, zirconium oxide, magnesium oxide, mullite, or cordierite. The second polymeric material includes at least one selected from nitrile rubber, polyvinyl chloride, polypropylene, polyvinyl alcohol, polyethylene, or polyvinylidene fluoride polymer. The inorganic particles can increase the surface roughness, thereby enabling the separator and electrode plates to form better liquid absorption channels, thus improving the liquid absorption rate.
[0093] In the technical solution of this application embodiment, the relationship between the electrolyte absorption rate a of the first coating 2312 and the electrolyte absorption rate b of the second coating 2313 satisfies: 0 mm / s 0.5 <ba≤5mm / s 0.5 .
[0094] The electrolyte absorption rate of the first coating 2312 refers to the height the electrolyte can climb on the positive electrode side per unit time. The electrolyte absorption rate of the second coating 2313 refers to the height the electrolyte can climb on the negative electrode side per unit time. The testing process can be as follows: After the separator 231 and the electrode sheet are combined, they are placed in an acrylic mold and pressurized to 3.5 MPa. Then, the acrylic mold is immersed in 1 mm to 2 mm of electrolyte to test the absorption rate. The climbing height is recorded at regular intervals. Then, the square root of time is plotted to obtain the absorption rate graph with height on the vertical axis and square root of seconds on the horizontal axis. The electrolyte absorption rate of the coating can be obtained. It should be noted that during the testing process, only a single coating is tested. For example, when testing the liquid absorption rate on the positive electrode side, the positive electrode 232 is bonded to the side of the separator 231 where the first coating 2312 is provided for testing (the negative electrode 233 is not present during the test); when testing the liquid absorption rate on the negative electrode side, the negative electrode 233 is bonded to the side of the separator 231 where the second coating 2313 is provided for testing (the positive electrode 232 is not present during the test).
[0095] By controlling the difference in electrolyte absorption rate between the second coating 2313 and the first coating 2312 to be within 0–5 mm / s 0.5 This allows for better matching of the electrolyte requirements of the negative electrode 233 and the positive electrode 232, enabling more efficient use of the electrolyte and further reducing electrolyte consumption.
[0096] For example, the difference in electrolyte absorption rate between the second coating 2313 and the first coating 2312 can be 0.1 mm / s. 0.5 0.5mm / s 0.5 1mm / s 0.5 1.5mm / s 0.5 2mm / s 0.5 2.5mm / s 0.5 3mm / s 0.5 3.5mm / s 0.5 4mm / s 0.5 4.5mm / s 0.5 5mm / s 0.5 etc., which can also be 0-5 mm / s 0.5 Any value within the range.
[0097] In the technical solution of this application embodiment, the electrolyte absorption rate 'a' of the first coating 2312 is 0.1 mm / s. 0.5 ~2mm / s 0.5 The second coating 2313 has an electrolyte absorption rate b of 2 mm / s. 0.5 ~5mm / s 0.5 The electrolyte absorption rate α of the first coating 2312 is controlled to be 0.1 mm / s. 0.5 ~2mm / s 0.5 The second coating 2313 has an electrolyte absorption rate b of 2 mm / s. 0.5 ~5mm / s 0.5 It can better match the electrolyte requirements of the negative electrode 233 and the positive electrode 232, so that the electrolyte can be fully utilized, thereby reducing the use of electrolyte and improving the cycle performance of the secondary battery 100.
[0098] For example, the electrolyte absorption rate α of the first coating 2312 can be 0.1 mm / s. 0.5 0.3mm / s 0.5 0.5mm / s 0.5 0.7mm / s 0.5 1mm / s 0.5 1.2mm / s 0.5 1.5mm / s 0.5 1.7mm / s 0.5 2mm / s 0.5 It can also be 0.1 mm / s. 0.5 ~2mm / s 0.5 Any value within the range. The electrolyte absorption rate b of the second coating 2313 can be 2 mm / s. 0.5 2.5mm / s 0.5 3mm / s0.5 3.5mm / s 0.5 4mm / s 0.5 4.5mm / s 0.5 5mm / s 0.5 It can also be 2mm / s. 0.5 ~5mm / s 0.5 Any value within the range.
[0099] This application does not impose any particular restrictions on the type of base membrane 2311, and any known porous structure base membrane 2311 with good chemical and mechanical stability can be selected.
[0100] In some embodiments, the base film 2311 may be made of at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The base film 2311 may be a single-layer film or a multi-layer composite film, without particular limitation. When the base film 2311 is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0101] In the technical solution of this application embodiment, the height of the positive electrode 232 along the first direction X is not less than 100mm; the height of the negative electrode 233 along the first direction X is not less than 100mm.
[0102] The higher the height of the electrode plates, the better it is to increase the capacity of the secondary battery. Controlling the height of the positive electrode plate 232 to be no less than 100mm and the height of the negative electrode plate 233 to be no less than 100mm can enable the secondary battery to have a higher capacity.
[0103] Furthermore, along the first direction X, the height of the positive electrode is 100mm to 600mm; along the first direction X, the height of the negative electrode is 100mm to 600mm. The higher the height of the electrode (and the higher the corresponding heights of the positive electrode 232 and negative electrode 233), the greater the probability of active metal deposition at its top, and the more prone it is to the phenomenon of cyclic dripping. By setting a first coating 2312 and a second coating 2313 containing liquid-absorbing material on both surfaces of the base film 2311, the problem of active metal deposition in the taller electrode assembly 23 can be effectively improved, thereby improving the problem of cyclic dripping.
[0104] For example, the height of the positive electrode 232 can be 100mm, 150mm, 200mm, 250mm, 300mm, 350mm, 400mm, 450mm, 500mm, 550mm, 600mm, etc., or any value within the range of 100mm to 600mm. The height of the negative electrode 233 can be 100mm, 150mm, 200mm, 250mm, 300mm, 350mm, 400mm, 450mm, 500mm, 550mm, 600mm, etc., or any value within the range of 100mm to 600mm. Further, along the first direction X, the height of the positive electrode is 300mm to 600mm; along the first direction X, the height of the negative electrode is 300mm to 600mm.
[0105] The positive electrode 232 includes a positive current collector and a positive active material layer. The positive active material layer is coated on the surface of the positive current collector. The positive current collector without the positive active material layer protrudes from the positive current collector with the positive active material layer. The positive current collector without the positive active material layer serves as the positive electrode tab.
[0106] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0107] In some embodiments, when the secondary battery 100 is a lithium-ion battery, the positive electrode active material may be a positive electrode active material known in the art for lithium-ion batteries. As an example, the positive electrode active material may include at least one of the following materials: lithium phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, this application is not limited to these materials, and other conventional materials that can be used as battery positive electrode active materials may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides include, but are not limited to, lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, and lithium nickel cobalt manganese oxides (such as LiNi). 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also known as NCM)333 LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM) 523 LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM) 211 LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM) 622 LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM) 811 At least one of lithium nickel cobalt aluminum oxides and their modified compounds. Examples of lithium-containing phosphates with an olivine structure include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, and lithium manganese iron phosphate and carbon composites.
[0108] In some embodiments, when the secondary battery 100 is a sodium-ion battery, the positive electrode active material may be a positive electrode active material known in the art for sodium-ion batteries. As examples, at least one of sodium transition metal oxides, polyanionic compounds, and Prussian blue compounds may be used. However, this application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium-ion batteries may also be used.
[0109] As an optional technical solution in this application, the transition metal in the sodium transition metal oxide can be at least one selected from Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. For example, the sodium transition metal oxide is Na. x M02, where M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr, and Cu, 0 <x≤1。
[0110] As an optional technical solution in this application, the polyanionic compound can be a compound containing sodium ions, transition metal ions, or a tetrahedral (YO4) structure. n- A class of compounds with anionic units. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; Y can be at least one of P, S, and Si; n represents (Y04). n- The price state.
[0111] Polyanionic compounds can also contain sodium ions, transition metal ions, or tetrahedral (YO4) ions. n- A class of compounds containing anionic units and halide anions. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; Y can be at least one of P, S, and Si, and n represents (YO4). n- The valence state; the halogen can be at least one of F, Cl and Br.
[0112] Polyanionic compounds can also be sodium-containing tetrahedral (YO4) compounds. n- Anionic unit, polyhedral unit (ZO) y ) n+ And a class of compounds with optional halide anions. Y can be at least one of P, S, and Si, and n represents (Y04). n- The valence state; Z represents a transition metal, which can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; m represents (ZO) y ) n+ The valence state; the halogen can be at least one of F, Cl and Br.
[0113] Polyanionic compounds include, for example, NaFePO4, Na3V2(PO4)3, NaM'PO4F (where M' is one or more of V, Fe, Mn, and Ni) and Na3(VO y )2(PO4)2F 3-2y At least one of (0≤y≤1).
[0114] Prussian blue compounds can be a class of compounds containing sodium ions, transition metal ions, and cyanide ions (CN-). The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. Examples of Prussian blue compounds include Na. a Me b Me' c (CN)6 where Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co, and Zn, 0 <a≤2,0<b<1,0<c<1。
[0115] In some embodiments, the positive electrode active material layer may optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0116] In some embodiments, the positive electrode active material layer may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0117] In some embodiments, the positive electrode 232 can be prepared by dispersing the components used to prepare the positive electrode 232, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g. N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive current collector, and then drying, cold pressing and other processes to obtain the positive electrode 232.
[0118] The negative electrode 233 includes a negative electrode current collector and a negative electrode active material layer. The negative electrode active material layer is coated on the surface of the negative electrode current collector. The negative electrode current collector without the negative electrode active material layer protrudes from the negative electrode current collector with the negative electrode active material layer coated on it. The negative electrode current collector without the negative electrode active material layer coated on it serves as the negative electrode tab.
[0119] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0120] In some embodiments, the negative electrode active material layer includes a negative electrode active material, which may be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. Silicon-based materials may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0121] In some embodiments, the negative electrode active material layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0122] In some embodiments, the negative electrode active material layer may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0123] In some embodiments, the negative electrode active material layer may also optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0124] In some embodiments, the negative electrode 233 can be prepared by dispersing the components used to prepare the negative electrode 233, such as negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto a negative electrode current collector, and then drying, cold pressing and other processes to obtain the negative electrode 233.
[0125] In other embodiments, the current collector of the negative electrode 233 may also include a current collector body and a base coating. The base coating may be disposed on at least one side of the current collector body. The base coating basically does not contain negative electrode active material, but may contain a small amount of carbon material. However, the carbon material forms a thin coating and cannot function as a negative electrode active material. In this embodiment, the negative electrode 233 can be an electrode without a negative electrode active material layer. For a negative electrode 233 without a negative electrode active material layer, when the current collector of the negative electrode 233 does not contain a base coating, the film layer of the negative electrode 233 can be disposed on the surface of at least one side of the current collector body; when the current collector of the negative electrode 233 includes a base coating, the film layer of the negative electrode 233 can be disposed on the surface of the base coating away from the current collector body.
[0126] In some implementations, in order to ensure that a large current can pass through without melting, there are multiple positive electrode tabs stacked together, and multiple negative electrode tabs stacked together.
[0127] In the technical solution of this application embodiment, the amount of electrolyte used is 2.0 g / Ah to 6.0 g / Ah. By differentiating the first coating and the second coating, the electrolyte requirements of the negative electrode and the positive electrode can be matched, so that the electrolyte can be fully utilized, thereby reducing the amount of electrolyte used.
[0128] For example, the amount of electrolyte can be 2g / Ah, 2.5g / Ah, 3g / Ah, 3.5g / Ah, 4g / Ah, 4.5g / Ah, 5g / Ah, 5.5g / Ah, 6g / Ah, etc., or it can be any value in the range of 2.0g / Ah to 6.0g / Ah.
[0129] In some embodiments, the electrolyte includes an electrolyte salt and a solvent.
[0130] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0131] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0132] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0133] [Preparation methods for battery cells]
[0134] Having introduced the materials and structure of battery cells, the following section will provide a detailed description of the preparation methods for battery cells.
[0135] Figure 2 For flowcharts of methods provided in some embodiments of this application, please refer to [link / reference]. Figure 2 The method for preparing a single battery cell provided in this application includes the following steps:
[0136] S1. Prepare the first polymer material into a first slurry.
[0137] S2. The second polymer material and inorganic particles are formulated into a second slurry. The second polymer material and inorganic particles can be mixed together to form one slurry, or they can be formulated separately into two slurries.
[0138] It should be noted that steps S1 and S2 can be interchanged or performed simultaneously, and this application does not impose any restrictions.
[0139] S3. The first slurry and the second slurry are respectively coated on both sides of the base film to form a first coating and a second coating, respectively, to obtain a release film, wherein the roughness of the second coating is greater than that of the first coating. It should be noted that when there are two slurries as the second slurry, they are coated separately.
[0140] The coating method can be: scraping, roller coating, slot coating, etc., and this application does not limit it.
[0141] S4. Assemble the separator, positive electrode, and negative electrode, and bring the electrolyte into contact with at least a portion of the positive electrode, separator, and negative electrode to obtain a battery cell, wherein the positive electrode is disposed on the side of the separator near the first coating and the negative electrode is disposed on the side of the separator near the second coating.
[0142] In some embodiments, the second coating includes an inorganic particle coating 2313a and a second polymeric adhesive layer 2313b. Specifically, an inorganic particle slurry can be first coated on the negative electrode side of the base film, and after drying, an inorganic particle coating 2313a can be formed; then, a second polymeric slurry can be coated on the surface of the inorganic particle coating 2313a, and after drying, a second polymeric adhesive layer 2313b can be formed. Alternatively, the second polymeric slurry can be coated on the negative electrode side of the base film, and after drying, a second polymeric adhesive layer 2313b can be formed; then, an inorganic particle slurry can be coated on the surface of the second polymeric adhesive layer 2313b, and after drying, an inorganic particle coating 2313a can be formed.
[0143] The assembly of the separator, positive electrode, and negative electrode can be either wound or stacked. Specifically, the separator, positive electrode, separator, and negative electrode are stacked sequentially, wound to form a flat structure, and then hot-pressed to obtain a wound electrode assembly; or, after preparing the positive electrode, the positive electrode, separator, negative electrode, separator, and so on are stacked sequentially to form a stacked electrode assembly.
[0144] Figure 3 This is a schematic diagram of the structure of a battery cell 20 provided in some embodiments of this application. Figure 4 Exploded views of a battery cell 20 provided for some embodiments of this application. Please refer to... Figure 3 and Figure 4 The battery cell 20 may include a housing 21, an end cap assembly 22, and an electrode assembly 23. The housing 21 has an opening 211, the electrode assembly 23 is housed within the housing 21, and the end cap assembly 22 is used to seal the opening 211.
[0145] The shape of the outer casing 21 can be determined according to the specific shape of the electrode assembly 23. For example, if the electrode assembly 23 is a cuboid structure, the outer casing 21 can be a cuboid structure. Figure 3 and Figure 4An example is shown where the housing 21 and electrode assembly 23 are square.
[0146] The outer shell 21 can also be made of various materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, etc. This application embodiment does not impose any special restrictions on this.
[0147] The end cap assembly 22 includes an end cap 221 and electrode terminals 222. The end cap assembly 22 is used to seal the opening 211 of the housing 21 to form a sealed mounting space (not shown) for accommodating the electrode assembly 23. The mounting space also accommodates an electrolyte, such as an electrolyte solution. As a component that outputs electrical energy to the electrode assembly 23, the end cap assembly 22 has electrode terminals 222 for electrical connection to the electrode assembly 23, specifically, the electrode terminals 222 are electrically connected to the tabs of the electrode assembly 23. For example, the electrode terminals 222 and the tabs are connected via a current collector 24 to achieve the electrical connection between the electrode terminals 222 and the tabs.
[0148] It should be noted that the opening 211 of the outer casing 21 can be one or two. If the outer casing 21 has one opening 211, the end cap assembly 22 can also be one, and two electrode terminals 222 can be provided in the end cap assembly 22. The two electrode terminals 222 are used to electrically connect to the positive electrode tab and the negative electrode tab of the electrode assembly 23, respectively. If the outer casing 21 has two openings 211, for example, the two openings 211 are located on opposite sides of the outer casing 21, the end cap assembly 22 can also be two, and the two end cap assemblies 22 respectively cover the two openings 211 of the outer casing 21. In this case, the electrode terminal 222 in one end cap assembly 22 can be a positive electrode terminal, used to electrically connect to the positive electrode tab of the electrode assembly 23; the electrode terminal 222 in the other end cap assembly 22 can be a negative electrode terminal, used to electrically connect to the negative electrode plate of the electrode assembly 23.
[0149] In some embodiments, such as Figure 4 As shown, the battery cell 20 may further include an insulating protective member 25 fixed to the outer periphery of the electrode assembly 23. The insulating protective member 25 is used to insulate and isolate the electrode assembly 23 from the housing 21. Exemplarily, the insulating protective member 25 is adhesive tape bonded to the outer periphery of the electrode assembly 23. In some embodiments, there are multiple electrode assemblies 23, and the insulating protective member 25 surrounds the outer periphery of multiple electrode assemblies 23, forming a single integral structure to maintain the structural stability of the electrode assembly 23.
[0150] [Rechargeable Battery]
[0151] In this application, the secondary battery 100 can refer to a single battery cell 20, or it can refer to a single physical module comprising multiple battery cells 20 to provide higher voltage and capacity, which can be in the form of a battery pack, battery module, etc. The secondary battery 100 may include a housing 10 for encapsulating multiple battery cells 20, and the housing 10 can prevent liquids or other foreign objects from affecting the charging or discharging of the battery cells 20.
[0152] Figure 5 This is an exploded structural diagram of a secondary battery 100 provided in some embodiments of this application. Please refer to... Figure 5 The secondary battery 100 includes a housing 10 and a battery cell 20, with the battery cell 20 housed within the housing 10.
[0153] The housing 10 provides a receiving space 11 for the battery cell 20. In some embodiments, the housing 10 may include a first portion 12 and a second portion 13, which overlap each other to define the receiving space 11 for accommodating the battery cell 20. Of course, the connection between the first portion 12 and the second portion 13 may be sealed by a sealant (not shown), such as a sealing ring, sealant, etc.
[0154] The first part 12 and the second part 13 can be of various shapes, such as cuboids, cylinders, etc. The first part 12 can be a hollow structure with an opening on one side to form a cavity for accommodating the battery cell 20, and the second part 13 can also be a hollow structure with an opening on one side to form a cavity for accommodating the battery cell 20. When the opening side of the second part 13 covers the opening side of the first part 12, a housing 10 with an accommodating space 11 is formed. Of course, as... Figure 5 As shown, the first part 12 can also be a hollow structure with an opening on one side, and the second part 13 can be a plate-like structure. The second part 13 covers the opening side of the first part 12, thus forming a box 10 with a accommodating space 11.
[0155] In the secondary battery 100, there can be one or more battery cells 20. If there are multiple battery cells 20, they can be connected in series, parallel, or in a mixed configuration. A mixed configuration means that multiple battery cells 20 are connected in both series and parallel. Multiple battery cells 20 can be directly connected in series, parallel, or in a mixed configuration, and then the whole assembly of multiple battery cells 20 is housed in the housing 10. Alternatively, multiple battery cells 20 can first be connected in series, parallel, or in a mixed configuration to form a battery module, and then multiple battery modules can be connected in series, parallel, or in a mixed configuration to form a whole assembly, which is then housed in the housing 10. The battery cell 20 can be cylindrical, flat, cuboid, or other shapes. Figure 5 An example is shown where the battery cell 20 is square.
[0156] In some embodiments, the secondary battery 100 may further include a busbar (not shown), through which multiple battery cells 20 can be electrically connected to each other to achieve series, parallel, or mixed connection of multiple battery cells 20.
[0157] The battery cell or secondary battery can be used in electrical equipment such as vehicles, ships, or aircraft. The power system of such electrical equipment can be constructed using the battery cells disclosed in this application.
[0158] [Electrical Equipment]
[0159] This application provides an electrical device that uses a battery as a power source. The electrical device can be, but is not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc.
[0160] For ease of explanation, the following embodiments will use a vehicle as an example of an electrical device according to an embodiment of this application.
[0161] Please refer to Figure 6 , Figure 6 This is a schematic diagram of the structure of a vehicle provided in some embodiments of this application. The vehicle 1000 can be a gasoline-powered vehicle, a natural gas-powered vehicle, or a new energy vehicle. New energy vehicles can be pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles, etc. A secondary battery 100 is installed inside the vehicle 1000, and the secondary battery 100 can be located at the bottom, front, or rear of the vehicle 1000. The secondary battery 100 can be used to power the vehicle 1000; for example, the secondary battery 100 can serve as the operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 300 and a motor 200. The controller 300 is used to control the secondary battery 100 to supply power to the motor 200, for example, to meet the power needs of the vehicle 1000 during startup, navigation, and driving.
[0162] In some embodiments of this application, the secondary battery 100 can not only serve as the operating power source for the vehicle 1000, but also as the driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.
[0163] The following examples will describe one or more embodiments in more detail. Of course, these examples do not limit the scope of the one or more embodiments.
[0164] Example 1
[0165] Preparation of positive electrode 232
[0166] A positive electrode slurry was prepared by thoroughly mixing lithium iron phosphate (LFP), conductive carbon black, polyvinylidene fluoride (PVDF), and N-methylpyrrolidone (NMP) at a mass ratio of 96.9:1:0.8:1.3. The positive electrode slurry was then subjected to a concentration of 310 mg / 1540.25 mm. 2 The loading amount is uniformly coated on the positive current collector aluminum foil, and then dried, cold pressed and cut to obtain the positive electrode sheet 232.
[0167] Preparation of negative electrode 233
[0168] Graphite, conductive carbon black, styrene-butadiene rubber (SBR) binder, and sodium carboxymethyl cellulose (CMC-Na) thickener were added to deionized water in a mass ratio of 96:1.5:1.5:1, and the mixture was thoroughly stirred and mixed to prepare an anode slurry (solid content 65%). This anode slurry was then applied at a concentration of 140 mg / 1540.25 mm. 2 The weight of the coating is applied to the copper foil of the negative electrode current collector, and then dried, cold-pressed and slit to obtain the negative electrode sheet 233.
[0169] Preparation of Electrolyte
[0170] Ethyl carbonate (EC), methyl ethyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to obtain an organic solvent. Then, fully dried LiPF6 was dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0171]
Isolation Membrane 231
[0172] Porous polyethylene membrane was used as the base membrane 2311.
[0173] A first slurry was prepared by mixing acrylonitrile rubber (a first polymer material) with N-methylpyrrolidone (NMP) at a mass ratio of 80:20, and then coated onto one side of a base film 2311 to form a first coating 2312. The coating amount of the first coating was 0.25 mg / 1540.25 mm. 2 The roughness Ra of the first coating is 0.25 μm.
[0174] Inorganic particulate silica, nitrile rubber (a second polymer material), and N-methylpyrrolidone (NMP) were mixed in a mass ratio of 80:10:10 to form a second slurry, which was then coated on the other side of the base film 2311 to form a second coating 2313. The coating amount of the second coating was 0.5 mg / 1540.25 mm. 2 The median particle size Dv50 of the inorganic silica particles is 0.9 μm, and the roughness Ra of the second coating is 0.51 μm.
[0175] Preparation of Secondary Battery 100
[0176] The positive electrode 232, separator 231, and negative electrode 233 are stacked and wound in sequence to obtain the electrode assembly 23. The positive electrode 232 is located on the side of the separator 231 closest to the first coating 2312, and the negative electrode 233 is located on the side of the separator 231 closest to the second coating 2313. The height of the motor assembly is 199.2 mm. The electrode assembly 23 is placed in an outer packaging, dried, and then injected with electrolyte. After vacuum sealing, settling, formation, and shaping processes, a secondary battery 100 is obtained.
[0177] Example 2
[0178] In this embodiment, the loading of the second coating is 1 mg / 1540.25 mm. 2 Meanwhile, apart from the roughness Ra of the second coating changing to 0.8 μm, everything else is the same as in Example 1.
[0179] Example 3
[0180] In this embodiment, the loading of the second coating is 1.5 mg / 1540.25 mm. 2 Meanwhile, apart from the roughness Ra of the second coating changing to 1.2 μm, all other aspects are the same as in Example 1.
[0181] Example 4
[0182] In this embodiment, except that the median particle size Dv50 of silicon dioxide is 1.3 μm and the roughness Ra of the second coating changes to 1.5 μm, everything else is the same as in Example 1.
[0183] Example 5
[0184] In this embodiment, except that the median particle size Dv50 of silicon dioxide is (1.8 μm) and the roughness Ra of the second coating changes to 2 μm, everything else is the same as in Example 1.
[0185] Example 6
[0186] In this embodiment, the loading of the first coating is 0.5 mg / 1540.25 mm. 2 Meanwhile, except that the roughness Ra of the first coating changes to 0.32 μm, all other aspects are the same as in Example 3.
[0187] Example 7
[0188] In this embodiment, except for the second coating which is layered, all other aspects are the same as in Embodiment 6. Specifically, the second coating is layered as follows: inorganic particulate silica, nitrile rubber, and N-methylpyrrolidone (NMP) are mixed in a mass ratio of 80:10:10 to form a second slurry. This second slurry is then coated onto the other side of the base film 2311 to form an inorganic particulate coating. A second polymer material, nitrile rubber, is mixed with N-methylpyrrolidone (NMP) in a mass ratio of 80:20 to form a third slurry. This third slurry is then coated onto the surface of the inorganic particulate coating 2313a to form a second polymer adhesive layer. The loading of the second polymer adhesive layer is 0.25 mg / 1540.25 mm. 2 The loading of the second coating was 0.5 mg / 1540.25 mm. 2 .
[0189] Example 8
[0190] In this embodiment, except that the height of the electrode assembly is 300mm, everything else is the same as in Embodiment 1.
[0191] Example 9
[0192] In this embodiment, in addition to reducing the amount of inorganic particles, the loading of the second coating and the first coating is the same (0.5mg / 1540.25mm). 2 Except for ), the rest of the content is the same as in Example 6.
[0193] Example 10
[0194] In this embodiment, except that the first polymer material and the second polymer particles are changed to polyvinyl alcohol, everything else is the same as in Example 6.
[0195] Example 11
[0196] In this embodiment, except that inorganic particulate silicon dioxide is replaced with aluminum oxide, everything else is the same as in Example 6.
[0197] Comparative Example 1
[0198] In this comparative example, except that the second coating is adjusted to be the same as the first coating, all other contents are the same as in Example 1.
[0199] Comparative Example 2
[0200] In this comparative example, except that the first coating and the second coating are the same, all other contents are the same as in Example 1.
[0201] The main parameter control and electrolyte absorption rate of each layer in combination with the electrode plates in Examples 1 to 11 and Comparative Examples 1 to 2 are shown in the table below:
[0202]
[0203] In the table, " / " indicates that the substance or the limitation does not exist. 'a' refers to the liquid absorption rate when the separator is coupled with the positive electrode. 'b' refers to the liquid absorption rate when the separator is coupled with the negative electrode.
[0204] The roughness testing process is as follows: The secondary batteries provided in the examples and comparative examples are disassembled, a portion of the battery assembly is cut off, and the positive and negative electrode plates are peeled off. Then, the roughness of the first and second coatings is tested using a laser online thickness gauge with reference to "GB / T1031-2009 Surface Structure Profile Method Surface Roughness Parameters and Their Values".
[0205] The liquid absorption rate test process is as follows: After the separator and electrode sheet are combined, they are placed in an acrylic mold and pressurized to 0.2 MPa. Then, the acrylic mold is immersed in 2 mm of electrolyte for the liquid absorption rate test. The liquid climbing height is recorded at regular intervals, and then the square root of time is plotted to obtain the liquid absorption rate graph with height on the vertical axis and square root of seconds on the horizontal axis, thus obtaining the liquid absorption rate of the coating to the electrolyte. It should be noted that during the test, only a single coating is tested at a time. That is, when testing the liquid absorption rate of the first coating with the positive electrode sheet, the negative electrode sheet of the electrode assembly is peeled off before testing, and when testing the liquid absorption rate of the second coating with the negative electrode sheet, the positive electrode sheet of the electrode assembly is peeled off before testing.
[0206] The secondary battery 1000 provided in each embodiment and comparative example was tested, and the tests included:
[0207] Cycle retention test: Battery cycle life test: Perform the following steps: a) Charge the battery at a constant current of 1C to 3.65V, then switch to constant voltage charging, and stop charging when the charging current drops to 0.05C; b) Discharge the battery at a constant current of 1C to 2.5V, then stop discharging; c) Repeat the charge-discharge cycle until the battery capacity drops to 85% of the initial capacity, then stop the test and record the number of cycles.
[0208] The test results are shown in the table below:
[0209]
[0210] As shown in the table above, by controlling the roughness of the second coating to be greater than that of the first coating, the liquid creep channel formed between the second coating and the negative electrode is better than that formed between the first coating and the positive electrode. This results in the liquid absorption rate on the negative electrode side being greater than that on the positive electrode side, which can match the electrolyte requirements of the negative and positive electrodes, quickly replenish the electrolyte on the negative electrode side, and make full use of the electrolyte, thereby improving the cycle performance of the secondary battery.
[0211] By comparing the data from Examples 1 to 5 and Examples 10 to 11, it can be seen that as the roughness of the second coating increases, the cycle performance of the secondary battery gradually improves. By controlling the roughness of the second coating to be above 0.5 μm, the number of cycles when the capacity of the secondary battery drops to 85% of the initial capacity can be above 600.
[0212] A comparison of the data from Examples 3 and 6 shows that, provided the negative electrode sheet is well wetted, the cycle performance of the secondary battery is better as the difference between the roughness Ra of the second coating and the roughness Ra of the first coating increases.
[0213] A comparison of the data from Examples 7 and 6 shows that using a layered arrangement of inorganic particles and organic materials is more beneficial to the cycle performance of the secondary battery.
[0214] A comparison of the data from Examples 1 and 8 shows that using a second coating with a roughness greater than that of the first coating improves the cycle performance of secondary batteries with higher electrode components.
[0215] The above are merely specific embodiments of this application and are not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A battery cell, characterized in that, The battery cell includes a positive electrode, a separator, a negative electrode, and an electrolyte; the separator includes a base film and a first coating and a second coating respectively located on the surface of the base film; the first coating is disposed between the positive electrode and the base film, and the second coating is disposed between the negative electrode and the base film; the electrolyte is in contact with at least a portion of the positive electrode, the separator, and the negative electrode. The roughness Ra of the second coating is greater than that of the first coating.
2. The battery cell according to claim 1, characterized in that, The difference between the roughness Ra of the second coating and the roughness Ra of the first coating is in the range of 0.25 μm to 1.85 μm.
3. The battery cell according to any one of claims 1 to 2, characterized in that, The roughness Ra of the second coating is 0.4 μm to 2.0 μm; and / or The roughness Ra of the first coating is 0.15 μm to 0.5 μm.
4. The battery cell according to any one of claims 1 to 3, characterized in that, The first coating comprises a first polymer material, and the second coating comprises a second polymer material and inorganic particles.
5. The battery cell according to any one of claims 1 to 4, characterized in that, The first coating includes a first polymer adhesive layer, the first polymer adhesive layer includes a first polymer material, and the mass percentage of the first polymer material in the first polymer adhesive layer is more than 90%. The second coating comprises an inorganic particle coating and a second polymer adhesive layer. The inorganic particle coating comprises inorganic particles, and the inorganic particles account for more than 90% of the mass of the inorganic particle coating. The second polymer adhesive layer comprises a second polymer material, and the second polymer material accounts for more than 90% of the mass of the second polymer adhesive layer.
6. The battery cell according to claim 5, characterized in that, The coating amount of the inorganic particles is 0.01 mg / 1540.25 mm. 2 ~1.25mg / 1540.25mm 2 ; and / or The coating amount of the second polymer adhesive layer is 0.25 mg / 1540.25 mm. 2 ~0.5mg / 1540.25mm 2 .
7. The battery cell according to claim 5, characterized in that, The inorganic particle coating is disposed between the second polymer adhesive layer and the base film of the separator.
8. The secondary battery according to any one of claims 4 to 7, characterized in that, The coating amount of the first coating is 0.25 mg / 1540.25 mm. 2 ~0.5mg / 1540.25mm 2 ; and / or The second coating has a coating thickness of 0.5 mg / 1540.25 mm. 2 ~1.5mg / 1540.25mm 2 ; and / or The median particle size Dv50 of the inorganic particles is 0.5 μm to 5 μm.
9. The battery cell according to any one of claims 4 to 8, characterized in that, The first polymeric material includes at least one of nitrile rubber, polyvinyl chloride, polypropylene, polyvinyl alcohol, polyethylene, or polyvinylidene fluoride polymers; and / or The inorganic particles include at least one of boehmite, silica, magnesium hydroxide, alumina, zirconium oxide, magnesium oxide, mullite, or cordierite; and / or The second polymeric material includes at least one of nitrile rubber, polyvinyl chloride, polypropylene, polyvinyl alcohol, polyethylene, or polyvinylidene fluoride polymer.
10. The battery cell according to any one of claims 1 to 9, characterized in that, The relationship between the electrolyte absorption rate 'a' of the first coating and the electrolyte absorption rate 'b' of the second coating satisfies: 0 mm / s 0.5 <ba≤5mm / s 0.5 .
11. The battery cell according to any one of claims 1 to 10, characterized in that, The first coating has an electrolyte absorption rate α of 0.1 mm / s. 0.5 ~2mm / s 0.5 ; and / or The second coating has an electrolyte absorption rate b of 2 mm / s. 0.5 ~5mm / s 0.5 .
12. The battery cell according to any one of claims 1 to 11, characterized in that, Along the first direction X, the height of the positive electrode is not less than 100 mm; and / or Along the first direction X, the height of the negative electrode sheet is not less than 100mm.
13. The battery cell according to claim 12, characterized in that, Along the first direction X, the height of the positive electrode is 100mm to 600mm; and / or Along the first direction X, the height of the negative electrode sheet is 100mm to 600mm.
14. The battery cell according to any one of claims 1 to 13, characterized in that, The amount of electrolyte used is 2.0 g / Ah to 6.0 g / Ah.
15. A method for preparing a single battery cell, characterized in that, The method includes: The first polymer material is formulated into a first slurry; The second polymer material and inorganic particles are formulated into a second slurry; The first slurry and the second slurry are respectively coated on both sides of the base film to form a first coating and a second coating, respectively, to obtain a separating film, wherein the roughness of the second coating is greater than that of the first coating; The separator, positive electrode, and negative electrode are assembled, and the electrolyte is brought into contact with at least a portion of the positive electrode, separator, and negative electrode to obtain a battery cell. The first coating is disposed between the positive electrode and the base film, and the second coating is disposed between the negative electrode and the base film.
16. A secondary battery, characterized in that, The secondary battery comprises a battery cell according to any one of claims 1 to 14 or a battery cell prepared by the method of claim 15.
17. An electrical appliance, characterized in that, The electrical equipment includes the secondary battery as described in claim 16.